CLINICAL AND BIOCHEMICAL CORRELATIONS OF HYPERURICEMIA IN ESSENTIAL HYPERTENSION. (June 2018) - Gruszka, K.; Rajzer, M.; Pizon, T.; Wojciechowska, W.; Czarnecka, D.
Abstract : Objective: Arterial hypertension and metabolic syndrome are clinical conditions leading to cardiovascular complications secondary to atherosclerosis. Hyperuricemia as a one of components of metabolic syndrome might directly damage arterial wall and cause atherosclerosis. Matrix metalloproteinases are involved in many processes associated in arterial wall damage and formation of atherosclerotic plaque.Their role in vascular pathology connected with hyperuricemia is unknown.Aim of the study was to identified clinical and biochemical differences between patients with mild primary arterial hypertension with and without of hyperuricemia with a particular evaluation of the wide spectrum matrix metalloproteinases serum activity. Design and method: Among patients with essential arterial hypertension (AH) stage 1 or 2 never treated by antihypertensive, hypolipemic or hypouricemic therapy we distinguished two groups.Asymptomatic hyperuricemia was defined as a serum uric acid over 356umol/l in females and over 416umol/l in males.The study participants were divided into two groups.Group 1 (G1) involves patients with asymptomatic hyperuricemia and AH, group 2 (G2) consisted of patients with normal uric acid and AH.We obtained in both groups anthropometric and clinical data including office and 24-hour ABPM. Several measures of subclinical organ damage were also obtained.In all the patients we assessed basic laboratory parameters and matrix metalloproteinases activity (MMP1, MMP2, MMP3, MMP9, TIMP1). Results: Hypertensive, hyperuricemia patients in G1–group have:higher diastolic and systolic nighttime blood pressure (SBP:119mmHg vs.113mmHg, p = 0.037;DBP:72mmHg vs.67mmHg, p = 0.043), BMI (29.75 kg/m2 vs.26.70 kg/m2, p = 0.002), higher waist circumference (97 cm vs.87 cm, p = 0.003) and higher triglycerides (1.56 mmol/l vs.1.20 mmol/l, p = 0.032), metalloproteinases 3 activity (MMP3) (19.41ng/ml vs.14.29ng/ml, p = 0.01) than patients without hyperuricemia in G2-group.Among analyzed subclinical organ damage parameters was observed negative correlation between decrease eGFR below90 ml/min/1, 73m2 and uric acid concentration (R = −0.37, p < 0.05).Considering analyzed MMPs activity only MMP3 activity was higher in G1 than G2.Serum uric acid concentration in univariate linear regression remained in significant association with MMP3 activity (R2 = 0.09, B = 0.3, p = 0, 002).This relationship was still significant after adjustment to age sex and BMI. Conclusions: Patient with essential arterial hypertension and hyperuricemia are characterized by higher prevalence of other metabolic syndrome components as a visceral obesity and hypertriglyceridemia.Uric acid concentration is associated with MMP3 activity, which is metalloproteinase initiating the cascade of other metalloproteinases responsible for degradation of structural vascular wall fibrous proteins.